Development of digital comic media: Reduce negative perceptions of guidance and counseling teachers - Triyanto, Agus; Setiani, Ismarini Bekti; Sari, Widya Juwita (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
This research started from a misunderstanding of the role and function of guidance and counseling teachers in schools from students, subject teachers, school principals, and even the general public. The roles and functions of guidance and counseling teachers are perceived negatively, which are assumptions and perspectives that are different from the actual roles and functions based on knowledge and professions that already exist in government regulations. The purpose of this study was to develop digital comic media as an effort to reduce negative perceptions of the role and function of guidance and counseling teachers in schools. This research is research and development with the Borg and Gall model. The subjects in this study were students of SMA N 5 Yogyakarta grades X, XI, and XII. Data collection using questionnaires and interview guidelines. Data analysis using quantitative analysis and qualitative analysis. This research produces a product in the form of digital comic media,, which has been validated by material experts and media experts as well as field trials on students. The resulting digital comics can be used as an interesting medium to change high school students' negative perceptions of the role and function of guidance and counseling teachers in schools.